Deciding on the priority of process parameters using the analytical hierarchy process in electrochemical wastewater treatment and investigation of paint wastewater treatability - Apaydin, Omer (ELSEVIER SCIENCE INC, 2024)
In planning electrochemical treatment processes, it is thought that decision-making tools should be used in the selection of the main parameters that are likely to affect pollutant removal. According to detailed research in the literature, no previous study has systematically prioritized process parameters in electrochemical wastewater treatment using the analytical hierarchy process (AHP). In this study, published articles in the literature on the subject were used to determine which parameters were used in the treatment processes and with what frequency. Using the obtained results, the priorities of the process parameters were estimated with the help of AHP within the scope of the removal efficiencies and treatment cost criteria. According to the AHP analysis results, it was determined that the most effective parameters for both electrocoagulation and electrooxidation processes were pH (0.241), current density (0.171), voltage (0.171), conductivity (0.107), concentration (0.105) and reaction time (0.094). Four of the independent parameters were selected and treatability studies were carried out using both electrocoagulation (with Al electrode pair and Fe electrode pair) and electro oxidation (with Graphite electrode pair and Ti electrode pair) methods for different levels of each parameter. The pH, current density, voltage, and reaction time were chosen as independent parameters based on decision making process. Unit costs for removal of chemical oxygen demand with Al, Fe, graphite, and Ti electrodes were obtained as 1.05, 2.56, 0.074, and 14 USD per m 3 wastewater, respectively. Unit costs for removal of color with Al, Fe, graphite, and Ti electrodes were obtained as 0.68, 1.20, 0.074, and 14 USD per m 3 of wastewater, respectively. In addition, nine batch kinetic studies were conducted for optimum conditions obtained from pre-treatment studies with Al and Fe electrodes. Removal of chemical oxygen demand was achieved at 64 % with aluminum and iron electrodes at 40 and 70 min, respectively. The results obtained from kinetic studies showed that adsorption of organic substances fit the 2nd-order kinetic model and the correlation coefficient was 0.95 and 0.96 for aluminum and iron electrodes, respectively.
Keywords: Analytical hierarchy process; Electrocoagulation; Electrooxidation; Paint industry wastewater; Adsorption; Treatment cost; ELECTROCOAGULATION PROCESS; LANDFILL LEACHATE; CHEMICAL COAGULATION; ANODIC-OXIDATION; OPTIMIZATION; REMOVAL; IRON; DECOLORIZATION; DEGRADATION; WASTEWATERS; Engineering; Water Resources